Who Pays Cigarette Taxes? The Impact of Consumer Price Search - DeCicca, Philip; Kenkel, Donald; Liu, Feng (The Review of Economics and Statistics, 2013)
We conduct an empirical study of the impact of consumer price search on the shifting of cigarette excise taxes to consumer prices. We use novel data on the prices that smokers report paying and document substantial price dispersion. We find that cigarette taxes are shifted at lower rates to carton buyers and, especially, smokers who buy cartons of cigarettes in a state other than their state of residence. We also find evidence that taxes are shifted at somewhat lower rates to the prices paid by heavier smokers and at somewhat higher rates to the prices paid by smokers of light cigarettes.